Synthesis of novel spiro[pyrazolo[4, 3-d]pyrimidinones and spiro[benzo[4, 5]thieno[2, 3-d]pyrimidine-2, 3′-indoline]-2′, 4(3H)-diones and their evaluation for anticancer activity. Issue 6 (15th March 2017) - Ismail; Kuthati, Bhaskar; Thalari, Gangadhar; Bommarapu, Venkatesham; Mulakayala, Chaitanya; Chitta, Suresh Kumar; Mulakayala, Naveen
Graphical abstract: Abstract: An efficient and novel method for the preparation of spiro[pyrazolo[4, 3- d ]pyrimidin]-7′(1′H)-ones by the condensation of 4-amino-1-methyl-3-propylpyrazole-5-carboxamide with ketones under mild conditions using catalytic InCl3 was reported. This method has been extended for the synthesis of novel spiro[benzo[4, 5]thieno[2, 3-d]pyrimidine-2, 3′-indoline]-2′, 4(3H)-dione which are having potential applications in medicinal chemistry. All the synthesized compounds were evaluated for their anti-proliferative properties in vitro against cancer cell lines and several compounds were found to be active. Further in vitro studies revealed that inhibition of sirtuins could be the possible mechanism of action of these molecules.